Design of Simulator to Evaluate Performance Parameters of Scheduling Clouds in Virtual Machine Environment (Global Journal of Computer Science and Technology, 2014)
Cloud computing acts as a vision of infinite computing resources that are provided on-demand to the cloud users as needed and are billed on pay as per usage basis Cloud computing employs the concept of virtualization that provides an opportunity to achieve business and IT objectives Scheduling is one of the most important challenges that a cloud computing environment faces Scheduling process determines the order of execution of jobs and the virtual machine to which job is assigned to execute so as to improve the performance and quality of service and at the same time resources are utilized effectively An attempt has been made in this paper to develop a simulator to schedule a job on allocated virtual machine so as to make efficient resource utilization In the proposed work scheduling is done on the basis of availability of allocated virtual machine providing equal capabilities We assumed that arrival of jobs in a cloud and their execution on a virtual machine is exponentially distributed For analysing the proposed algorithm the performance parameters of scheduling clouds are evaluated in Virtual Machine Environment
Keywords: cloud computing; job scheduling; simulator; exponential distribution; response parameters